2019
DOI: 10.2217/lmt-2018-0016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Non-Small-Cell Lung Cancer Patients Receiving Concurrent Metformin and Immune Checkpoint Inhibitors

Abstract: Aim: To study the clinical benefits of concurrent metformin and immune checkpoint inhibitors (ICIs) in non-small-cell lung cancer patients. Materials & methods: This is a retrospective review of 50 non-small-cell lung cancer patients receiving ICIs with metformin (cohort A) or without metformin (cohort B). Patients were also stratified by ICIs as second-/third-line therapy. Results: Overall response rate and disease control rate were higher in cohort A (41.1 vs 30.7%, p = 0.4 and 70.5 vs 61.6%, p = 0.5, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 62 publications
1
56
0
Order By: Relevance
“…The present evidence partly supports the use of metformin in combination with ICIs for improving the treatment of several cancers. This therapeutic schedule is also associated with a substantial risk of adverse effects ( 1 , 11 ). Various approaches are underway to expand the benefits and improve the efficacy of these ICIs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present evidence partly supports the use of metformin in combination with ICIs for improving the treatment of several cancers. This therapeutic schedule is also associated with a substantial risk of adverse effects ( 1 , 11 ). Various approaches are underway to expand the benefits and improve the efficacy of these ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the promoting effects of metformin on anti-PD-1/PD-L1 therapy in preclinical studies, more scientists are concentrating on the antitumor effects of metformin in combination with ICIs (as summarized in Table 1 ). Several studies observed favorable treatment outcomes (objective response rate, disease control rate, median progression-free survival, and median overall survival) in patients who received metformin in combination with ICIs without reaching a statistically significant trend ( 1 , 11 , 37 ). The subgroup analysis found a statistically significant association between metformin use and OS in obese patients with a BMI >25 kg/m 2 ; the strength of the association was higher in patients with a BMI >30 kg/m 2 ( 31 ).…”
Section: Metformin Influences the Antitumor Efficiency Of Icismentioning
confidence: 99%
See 2 more Smart Citations
“…Other compounds that can modulate PD-L1 expression could provide alternatives to antibodies with different pharmacological properties and toxicity profiles, which may be used in combinational therapy. For example, metformin induces degradation of PD-L1 through endoplasmic reticulum-associated (16) or other signaling pathways (17), and was shown to improve overall response and disease control rate in combination with checkpoint inhibitors in small clinical trials in NSCLC (18) and melanoma (19). Many natural compounds (e.g.…”
Section: Discussionmentioning
confidence: 99%